EXPLORING RAMADHAN MSME TRENDS AS A TOURIST ATTRACTION IN BATAM CITY - Arina Luthfini Lubis; Andri Wibowo; Zahara Fatimah; Yudha Wardani; Oktora Aji Pratama (RADJA PUBLIKA, 2025)
Ramadhan-based micro, small, and medium enterprises (MSME) grow rapidly in major cities as seasonal economic activities, yet their potential as culinary tourism attractions remains underexplored. This study aims to explore the potential of Ramadhan MSME in Batam City and propose development strategies within the framework of sustainable tourism. A mixed method approach was used, involving 195 tourist respondents through questionnaires and 30 vendors selected purposively for interviews. Data were gathered through field observation, documentation, and analyzed using descriptive and thematic techniques. Findings show that MSME activities peaked in the first three weeks of Ramadhan, with popular products including snacks and full meals. Most vendors were micro-enterprises managed independently, earning daily turnovers of IDR 500,000–1,000,000. Tourists valued service and the Ramadhan atmosphere as key attractions, although cleanliness and facilities need improvement. Pasar Mega Legenda was the most visited site. Recommended strategies include product innovation, integration into tourism packages, digital branding, and ongoing training. This study highlights that Ramadhan MSME have strong potential to become part of Batam’s inclusive, creative, and sustainable tourism ecosystem.